Clinical Correlation of Oblique Magnetic Resonance Imaging (MRI) for Cervical Foraminal Stenosis - Asghar Khan Babar, Irfan Adil, Reeta Rani, M Tameem Akhtar, Ruqqayia Adil, Mian Iftikhar Ul Haq, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Cervical foraminal stenosis frequently contributes to neck pain and radiating symptoms, which often leads to considerable discomfort and difficulty in performing daily activities. Despite routine use of MRI for diagnosis, it is unable to visualise the foraminal area clearly. Oblique MRI has been suggested as a better imaging assessment for quantifying nerve root compression, though its usefulness in practice is still being explored. The purpose of the study is to evaluate the clinical relationship of oblique magnetic resonance imaging findings with the symptoms reported in patients with cervical foraminal stenosis. Methods: This cross-sectional study was conducted on 54 patients presenting with signs of cervical radiculopathy between January 2022 to December 2022 at the Department of Neurosurgery, Sandeman Provincial Hospital/ Bolan Medical College Quetta. Detailed clinical assessments were recorded, including pain severity (VAS), functional status (NDI), and neurological examination. Each patient underwent cervical spine MRI with oblique T2-weighted sequences. The degree and side of foraminal stenosis were noted, and the relationship between clinical symptoms and imaging findings was statistically analyzed. Results: The C5–C6 and C6–C7 levels were most frequently affected. A significant correlation was observed between clinical symptoms and the side of stenosis on MRI (p = 0.012). Pain and disability scores were strongly associated with stenosis severity (p = 0.021 and p = 0.035, respectively). Spurling's test demonstrated high agreement with radiological findings (p = 0.009). Conclusion: Oblique MRI enhances the diagnostic accuracy for cervical foraminal stenosis by providing more precise visualization of the foraminal space. The strong clinical-radiological correlation observed in this study supports the inclusion of oblique imaging sequences in standard cervical MRI protocols, particularly for patients with radicular symptoms. Keywords: Cervical radiculopathy, Foraminal stenosis, Oblique MRI, Magnetic resonance imaging, Nerve root compression, Clinical correlation, Neck pain, T2-weighted imaging, Cervical spine, Diagnostic imaging.